DAMPAK PENERAPAN E-SPT MASA PPN TERHADAP EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK PERTAMBAHAN NILAI (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Malang Utara Tahun 2014-2018) - Zulfika Nur’aini; Nur Hidayati; Abdul Wahid Mahsuni (Universitas Islam Malang, 2019)
ABSTRACTThis research aims to know the policy of reporting e-VAT, in the application of PER-11 / PJ / 2013, e-PPN reporting, effectiveness after application PER-11 / PJ / 2013 on VAT, and the level of contribution after application PER-11 / PJ / 2013 on VAT, and barriers to VAT itself. This study uses descriptive qualitative approach. The results of this study are the regulations of the Directorate General of Taxes PER-11 / PJ / 2013 that make the administrative system that applies to the Services section, the Data and Information Processing section becomes more efficient. The number of e-PPN delivery reports is greater after the implementation of PER-11 / PJ / 2013. The amount of effectiveness and contribution of VAT is greater after the implementation of PER-11 / PJ / 2013. However, the level of effectiveness has a greater influence on value added tax revenue. As an example of supporting factors, the Primary Tax Office in North Malang is socialized to tax-affected employers, by providing consulting services, and providing information about tax compliance. For the inhibiting factor regarding the implementation of e-SPT, it consists of taxable entrepreneurs who are not well known about how to use the VAT e-SPT, and for the amount of attention about taxable entrepreneurs is still low. Keywords : Value Added Tax, e-VAT, Realization of acceptance, Target Revenues, Effectiveness, Contributions.